Criminal Act of Adultery Against Married Perpetrators Based on Qanun Aceh Number 6 of 2014 - Dainur, Dainur; Zarzani, Riza (PT. Multidisciplinary Press Indonesia, 2024)
This study examines the crime of adultery committed by individuals who are already married based on the provisions of Qanun Aceh No. 6 of 2014 concerning Jinayat Law. Qanun Jinayat, which enforces Islamic criminal law in Aceh, applies to all residents, both Muslims and non-Muslims, within the province. The primary objective of this qanun is to regulate society's behavior within the framework of Islamic law and to deter violations of Islamic principles through punitive measures, including fines, imprisonment, and flogging. The crime of adultery in Islam is classified into two categories: muhsan (those who have had legitimate sexual relations in marriage) and ghairu muhsan (those who have not). The punishment for muhsan includes stoning, while ghairu muhsan is punished by 100 lashes and exile. In contrast, under Qanun No. 6 of 2014, the punishment for adultery, regardless of the marital status of the offender, is 100 lashes without the distinction between muhsan and ghairu muhsan. Furthermore, the Qanun differs from Indonesia's national law (KUHP Article 284), which requires a formal complaint from the injured spouse for prosecution. In contrast, under Qanun Jinayat, no complaint is required for adultery cases to be prosecuted, and the penalties for those who facilitate or promote adultery are also included. The research also delves into a case study, Case No. 4/JN/2021/MS.Idi, where the perpetrator was sentenced to 100 lashes under Qanun Jinayat for committing adultery. The study compares the treatment of adultery under national law and Qanun Aceh and concludes that the Qanun provides harsher penalties to ensure deterrence and uphold Islamic values in Aceh.